Effects of Tai Chi training on static balance ability of elderly people: Based on different training volume - Li, Zhengming; Mao, Lihua; Zheng, Manjing (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Static balance refers to the body’s ability to maintain a posture or a stable state by adjusting its center of gravity in a relatively static state. The study of static balance ability in the elderly has been widely concerned. Balance is the ability to keep the center of gravity of the body above the supporting base plane. The center of gravity of the body changes as the posture changes and the body moves. When the human body stands still, the body is in a state of constant shaking around its own equilibrium point, and the subjective consciousness cannot control such shaking. In physiology, this phenomenon is called physiological posture shaking. Static balance ability of measurement methods at present is mainly by subjects stand on a stationary platform for biomechanics or tablet on the platform of the high sensitivity of force sensor can be used to record the subjects of the body, and after a series of analysis software to calculate the static balance evaluation parameters of human body balance. The evaluation parameters of static balance include the position of the center of gravity of the subject, the area of the center of gravity moving path or the area of the region, the total length of the center of gravity moving path, and the ratio of the center of gravity parameters when the subject is measured with eyes closed and eyes open, etc. The CoP (Center of pressure, CoP) of the human body in a static or slow moving state can be approximately equal to the center of gravity of the body. Therefore, COP related parameters were adopted in this study, which can be used as an indicator to evaluate patients’ balance ability. The effects of tai chi practice on balance in older adults have been reported in several previous studies. However, for the elderly, how to set the training amount to better promote the improvement of the static balance ability of the elderly is still a problem to be solved. Therefore, the purpose of this study is to investigated the internal mechanism of the influence of Tai Chi training on the static balance ability of the elderly by setting three different training volume of Tai Chi exercises. Methods: Thirty people over 65 years of age volunteered to participate in the study. All participants were subjected to strict medical screening to ensure that the selected subjects were in good health and had no lower limb muscle and joint injury within 3 months before the experiment. Besides, make sure they are physically and mentally able to withstand the test by sign the informed letter. And all participants are allowed to withdraw from the study at any time. Before the experiment, the subjects were clearly informed of the experiment process, the experiment requirements and the possible discomfort during the experiment. Before the formal experiment, the static balance ability of all subjects was measured by a force platform (AMTI, Watertown, USA, sampling frequency of 1000 Hz). Subjects first need to warm up in the running playground for 10 minutes. Immediately after the warm up, the subjects have 5 minutes to get fully familiar with the experimental environment and experimental instruments, and then collect the static balance ability of the dominant leg of the subjects. Under the guidance of the experiment personnel, the subject stands on the force platform with one leg supported by the dominant leg, and the knee joint of the other leg is bent 90 degrees. The subjects were asked to stand on one leg on a load bench for 30 seconds. During the data collection, the subjects were asked to look at a fixed area directly ahead. Combined with the results of the static balance test, the participants were divided into three groups (group A, B and C) with no significant difference. Participants in all three groups were asked to finish the Tai Chi Training 3 times a week continue 16 weeks. The group A was asked to finish 45 minute Tai Chi Training in each times, the group B and C was asked to finish 60 and 90 minute of Tai Chi Training in each times, respectively. At the end of the 16 weeks of tai chi training, the static balance ability of all three groups was measured again. In the process of experimental intervention, a professional martial arts teacher and a medical staff accompanied the whole process to ensure the smooth progress of the experiment and the safety of the subjects. In the measured of static balance ability, the subjects was asked to stands on the force platform under the guidance of experiment personnel, the index of static balance ability was measured and record to evaluate the static balance ability of the elderly. And the index was including: the average displacement velocity of CoP in the Antero-Posterior (AP) and Medium-Lateral (ML) axis, the area of the CoP, the maximum displacement of COP in AP and ML axis. If the value is low, it means that the static balance is good, and if the value is high, it means that the static balance is poor. All the experimental data were exported to Excel and calculated by MATLAB R2019a software. Calculate the CoP area, the maximum displacement of COP in the AP and ML axis, as well as the average displacement velocity of CoP in the AP and ML axis by editing the program code. The static balance ability data of the three groups of subjects were analyzed by one-way ANOVA using SPSS 25. 0 software. The boxplot was used to determine whether the data of each group were normal, and Shapiro-Wilk test was used to determine whether the data of each group obeyed an approximate normal distribution. Data were expressed in the form of Mean±SD, and the significance level of this study was set as P<0. 05. Results: The CoP area of group A, B and C were 701. 20±307. 13 mm2, 434. 71±241. 23 mm2 and 519. 46±251. 08 mm2, respectively. There were a statistically significant differences in the effect of A, B and C training amount on the CoP area of the subjects (P<0. 001). Compared with the group A, the CoP area of group B and C was significant small (P=0. 026). And there are no significant difference between group B and C (P=0. 077). The maximum displacement of COP in the ML axis of group A, B and C were 43. 67±4. 02, 39. 91±4. 94 and 31. 08±3. 13, respectively. There were a statistically significant differences in the effect of A, B and C training amount on the maximum displacement of COP in the ML axis of the subjects (P<0. 001). Compared with the group A and B, the maximum displacement of COP in the ML axis of group C was significant small (P=0. 019). And there are no significant difference between group A and B (P=0. 058). The maximum displacement of COP in the AP axis of group A, B and C were 24. 10±6. 44, 23. 51±3. 30 and 17. 11±3. 02, respectively. There were a statistically significant differences in the effect of A, B and C training amount on the maximum displacement of COP in the AP axis of the subjects (P<0. 001). Compared with the group A and B, the maximum displacement of COP in the Ap axis of group C was significant small (P=0. 341). And there are no significant difference between group A and B (P=0. 082). The average displacement velocity of CoP in the ML axis of group A, B and C were 915. 17±338. 90 mm/s, 971. 07±294. 66 mm/s and 894. 30±210. 13 mm/s. There was no statistically significant differences in the effect of A, B and C training amount on the average displacement velocity of CoP in the ML axis of the subjects (P=0. 641). The average displacement velocity of CoP in the AP axis of group A, B and C were 1021. 35±195. 102 mm/s, 997. 06±201. 03 mm/s and 890. 17±201. 91 mm/s. There was no statistically significant differences in the effect of A, B and C training amount on the average displacement velocity of CoP in the AP axis of the subjects (P=0. 790). Conclusion: The purpose of this study is to investigated the effect of Tai Chi training on the static balance ability of the elderly based on three different training volume of Tai Chi exercises. Through the study, we found that the static CoP area decreased gradually with the increase of training volume, but when it reached a certain level, the CoP area no longer showed a significant decrease. This means that the static balance ability will improve with the increase of the volume of Tai Chi training, however, after reaching 60 minutes each time, the static balance ability will not improve with the increase of the training volume. And for the maximum displacement of COP in AP and ML axis, when the training volume reaches 90 minutes each times, the maximum displacement of CoP in AP and ML axis was significantly lower, which means that the training volume should be increased to at least 90 minutes each times to reduced the swing of body. In addition, the increase of training volume of Tai Chi has no effect on the mean displacement velocity of CoP. Therefore, combination with the results of this study, it is recommended to set the amount of Tai Chi training at no less than 60 minutes each time for improve the static balance ability of the elderly.